Changes and Patterns in Mongolia-Russia Trade - Avirmed, Davaasuren (Institute of International Studies, 2024)
This article examines the historical and contemporary trends in Mongolia-Russia trade, their patterns, and the objective factors influencing them. It also analyzes the impact of the COVID-19 pandemic on the overall dynamics of Mongolia’s export potential and the quantity and value of key imported goods. The article explores the structure of Mongolia’s exports and imports, the role of regions such as Irkutsk Oblast, the Republic of Buryatia, Altai Krai, and Krasnoyarsk Krai in Mongolia-Russia border trade, as well as changes in trade relations between directly adjacent Russian regions and those without direct borders with Mongolia. Additionally, it highlights the specialization and diversification of certain types of goods in border trade between these regions. Монгол-Оросын худалдаанд гарч буй өөрчлөлтүүд ба тэдгээрийн зүй тогтол Хураангуй: Энэхүү өгүүлэлд Монгол, Оросын худалдааны түүхэн ба өнөө цагийн чиг хандлага, түүний зүй тогтол, нөлөөлж буй объектив хүчин зүйлс, Монгол Улсын экспортын чадавхи болон импортын гол нэр төрөл барааны тоо хэмжээ ба үнийн дүнгийн ерөнхий динамикт Ковид-19 цар тахалын үзүүлсэн нөлөө, Монгол Улсын экспорт болон импортын барааны бүтэц, Монгол, Оросын хил орчмын худалдаанд Эрхүү муж, Буриад Улс, Алтайн болон Красноярскийн хязгаар зэрэг субъектүүдийн гүйцэтгэж байгаа үүрэг, Монгол Улстай шууд залгаа хиллэдэг субъектүүд ба шууд хиллэдэггүй субъектүүдтэй хийж байгаа худалдаан дахь харьцааны өөрчлөлт, хил орчмын худалдаан дахь субъектүүдийн тодорхой төрлийн бараан дээр дагнаж, төрөлжсөн байдлыг бичсэн. Түлхүүр үгс: Монгол, Орос, худалдаа, экспорт, импорт, жонш, газрын тос, эрчим хүч, мах махан бүтээгдэхүүн, хүнсний бүтээгдэхүүн, хил орчмын худалдаа гэх мэт.